Water status and macronutrient concentrations, but not carbon status, of Viscum album ssp. album are determined by its hosts: a study across nine mistletoe–host pairs in central Switzerland - Wang, Ao; Bose, Arun K.; Lehmann, Marco M.; Rigling, Andreas; Gessler, Arthur; Yu, Longfei; Li, Maihe (Frontiers in Plant Science, 2023)
Introduction European mistletoe, Viscum album L., is a hemiparasite that can infect various tree species, yet our understanding of its physiological interactions with host species is limited. Methods Nine mistletoe–host pairs (i.e. V. album ssp. album growing on nine different broadleaf tree species) under different growth conditions in central Switzerland were selected to examine the carbon, water and nutrient relationships between mistletoe and its hosts. We measured leaf morphological traits, isotopic compositions (δ13C and δ15N), concentrations of non-structural carbohydrates (NSC) and specific compounds (i.e. mobile sugars and starch), and macronutrients (i.e. N, P, K, Ca, Mg, S) in leaf and xylem tissues of both mistletoe and its hosts. Results and Discussion There were only non-significant relationships between NSC concentrations in mistletoe and in its host species across the nine mistletoe–host pairs, suggesting the carbon condition of V. album ssp. album is determined by both the heterotrophic carbon transfer and self-photosynthetic capacity among different mistletoe-host pairs. However, mistletoe leaf morphological traits (single leaf area and mass, and leaf mass per unit leaf area) did not change across the nine mistletoe–host pairs, and mistletoe leaf δ13C, water content and macronutrient concentrations were linearly correlated with those in the host leaves. Macronutrients showed accumulations in mistletoe across the nine pairs. Further, tissue N concentrations were significantly higher in mistletoe grown on N-fixing hosts than on non-N-fixing hosts. Finally, leaf N:P in mistletoe was significantly correlated with the ratio in the host across the nine mistletoe–host pairs. Overall, our results indicate strong relationships between mistletoe and its hosts for water- and nutrient-related traits, but not for carbon-related traits, which demonstrates that V. album ssp. album can adjust its physiology to survive on different deciduous tree species hosts and under different site conditions.